The Russian Banking Sector: Unsolved Problems Seven Years after the Crisis - Alfred Steinherr; Erik Klär (Weekly Report, 2005)
The Russian foreign exchange and financial market crisis of summer 1998 was caused by international movements of capital following the Asian crisis, and it plunged the Russian commercial banks into major difficulties. Practically the entire banking sector was hit by acute liquidity shortage. The main cause of the banking crisis must be seen in the banking sector regulation, which was defective if not lacking altogether. This encouraged the banks to take big exchange rate risks on liabilities in foreign currencies, and to lend with little risk diversification, which proved fatal in the crisis. The method used by the Russian authorities to deal with the crisis was also unorthodox by western standards. The crisis was overcome without major restructuring in the banking sector and accomplished at astonishingly little cost to the economy as a whole. However, the success in the form of good growth rates in every year since 1998 only seemingly justifies this neglect, for the relatively weak constitution of the banking sector in Russia _ compared with other transition economies _ has certainly hampered even better economic development. Although some more recent legislative initiatives do give reason to hope for improvement here, powerful interests are still preventing the optimal restructuring of the banking scene that is necessary for the economy as a whole.
Keywords: 330